Variations in the Survival Probabilities of the PVC-Protected Red Mangrove Propagules: Testing the Encased Replanting Technique - López-Ortiz, Myrna I.; Pérez, Cynthia M.; Suárez, Erick; Ríos-Dávila, Rafael (Puerto Rico Health Sciences Journal, 2014)
see manuscript